1998
DOI: 10.1046/j.1365-2656.1998.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐interactive fish communities in the coastal streams of North‐western France

Abstract: Summary 0[ Spatial patterns of freshwater _sh species at regional and local scales were inves! tigated to explore the possible role of interspeci_c interactions in in~uencing dis! tribution and abundance within communities occupying coastal streams of North! Western France[ 1[ Nine sites from nine streams situated in the same biogeographical region were sampled annually over the 5!year period from 0889 to 0884[ 2[ Similar habitats "sites# with richer regional colonization pools exhibited pro! portionally riche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
2
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 41 publications
8
99
2
6
Order By: Relevance
“…Relative to this point, results of different studies previously detailed above show that local and regional fish communities are usually not saturated with species and are capable of supporting greater number of species if the pool of potential colonists and the rate of colonization from that pool was increased by species introduction (Belkessam et al, 1997;Angermeier and Winston, 1998;Oberdorff et al, 1998;Gido and Brown, 1999). These results strongly suggest that competition does not set the species saturation level in the assemblages studied and thus that competition is not a major force structuring these fish assemblages.…”
Section: Role Of Biotic Factors Competition and Predationmentioning
confidence: 70%
See 3 more Smart Citations
“…Relative to this point, results of different studies previously detailed above show that local and regional fish communities are usually not saturated with species and are capable of supporting greater number of species if the pool of potential colonists and the rate of colonization from that pool was increased by species introduction (Belkessam et al, 1997;Angermeier and Winston, 1998;Oberdorff et al, 1998;Gido and Brown, 1999). These results strongly suggest that competition does not set the species saturation level in the assemblages studied and thus that competition is not a major force structuring these fish assemblages.…”
Section: Role Of Biotic Factors Competition and Predationmentioning
confidence: 70%
“…competition, predation, disturbance) were the focus of studies seeking to explain local fish assemblage structure (Schlosser, 1995), emphasis on the role of regional processes has increased as some studies have demonstrated their pervasive role in shaping local assemblages Whittier et al, 1988;Hugheny and Paugy, 1995;Hugueny et al, 1997;Belkessam et al, 1997;Angermeier and Winston, 1998;Oberdorff et al, 1998). Consequently, complete answers for the explanation of local fish assemblage richness and structure must address the relative importance of large-scale processes, which determine the species available to occur locally and small-scale processes, which should limit the number of species that actually occur locally (Angermeier and Winston, 1998).…”
Section: Factors Structuring Riverine Fish Assemblages In Temperate Amentioning
confidence: 99%
See 2 more Smart Citations
“…En effet, chacune des espèces qui compose les peuplements étudiés réagit de façon différentielle aux variations environnementales (différence dans : les périodes de ponte et de recrutement, la distribution sur le gradient vertical, les habitats, la taille des individus et leurs vagilités...) et contribue de la sorte à faire augmenter la variabilité du peuplement à mesure que l'on augmente la durée du suivi. Par ailleurs, à l'échelle locale, les peuplements de poissons des cours d'eau semblent dépendre, en partie, de processus qui s'opèrent à l'échelle régionale (HUGUENY et PAU G Y, 1995 ;BELKESSAM et al, 1997 ;OBERDORFF et al, 1998). …”
Section: Discussionunclassified